2018
DOI: 10.1002/nau.23718
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for chronic neuropathic pain in patients with bladder pain syndrome/interstitial cystitis

Abstract: The results of this study show that rTMS applied with an H-coil over the M1 in the area corresponding to the pelvic region in patients with BPS/IC appears to improve chronic pelvic pain (CPP) and associated urinary disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 83 publications
(171 reference statements)
2
41
0
8
Order By: Relevance
“…Cortical centers involved in salience evaluation and control of the LUT can be therapeutically targeted for symptom remission in patients with pelvic floor dysfunction . Recently, targeting some of these centers—the primary motor cortex in the area corresponding to the pelvic region and the prefrontal cortices—with multisession rTMS provided proof‐of‐concept evidence of promising therapeutic effects. Specific to UCPPS and of the rTMS protocols tested in the current study, a protocol compromised of multisessions of the low‐intensity HF‐rTMS applied to SMA should be studied for its possible effectiveness in treating symptoms of UCPPS, when taking into consideration the observed changes in muscle and brain activity in the current study and structural and functional changes in SMA observed in patients with UCPPS .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cortical centers involved in salience evaluation and control of the LUT can be therapeutically targeted for symptom remission in patients with pelvic floor dysfunction . Recently, targeting some of these centers—the primary motor cortex in the area corresponding to the pelvic region and the prefrontal cortices—with multisession rTMS provided proof‐of‐concept evidence of promising therapeutic effects. Specific to UCPPS and of the rTMS protocols tested in the current study, a protocol compromised of multisessions of the low‐intensity HF‐rTMS applied to SMA should be studied for its possible effectiveness in treating symptoms of UCPPS, when taking into consideration the observed changes in muscle and brain activity in the current study and structural and functional changes in SMA observed in patients with UCPPS .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if exciting SMA reduces PFM tone and inhibiting SMA increases PFM tone, SMA is likely exerting an inhibitory influence on resting PFM tone. We expect that our preliminary study may provide hypotheses for further studies that seek to reduce PFM tone (eg, urologic pain) or increase PFM tone (eg, incontinence), including studies that seek to produce lasting effects on symptoms with repeated rTMS sessions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BPS is also frequently accompanied by urinary symptoms, including urgency, frequency, and nocturia (101,128). BPS is the cause of pain in more than 30% of women with chronic pelvic pain (CPP) (100). The mechanism of bladder pain and urinary problems is hypothesized to be associated with the misperceptions and improper integration of sensory information provided by bladder filling and central sensitization (101).…”
Section: Pelvic Painmentioning
confidence: 99%